Continuity of Conduct and Substance Use Disorders among Adolescents in the One Year and Two Years Following Exposure to Substance Abuse Treatment - McManus, Brian (2012)
The current study utilized a sample of 138 adolescents from a short-term inpatient chemical dependency recovery hospital. Analyses utilized scales from the Global Appraisal of Individual Needs (GAIN), a semi-structured interview that was administered multiple times over the two years after treatment intake. Analyses examined the persistence of substance abuse, conduct disorder symptomatology, delinquent behavior, and mental distress following treatment. A primary goal of the study was to examine whether adolescents with severe conduct disorder (i.e., those engaging in behaviors causing considerable harm to others) followed different trajectories than their mild/moderate counterparts. This inquiry was predicated largely on research that suggests two different pathways for delinquent behavior, namely life-course persistent versus adolescence-limited offending. Substance abuse was measured in terms of both frequency of use, as well as associated problems. The study also examined the presence of “minimal” (i.e., 10% or less of days) or “non-problem” use (i.e., active users reporting no symptoms of abuse or dependence). Overall, fewer mean substance-related problems were reported at each successive follow-up despite the fact that average frequency of substance use increased steadily from the around one-fifth of days at the 3-month follow-up to nearly half of all days at year-two. Results of multilevel negative binomial regression indicated that estimated number of conduct disorder symptoms changed significantly over time, with estimates for average number of conduct disorder symptoms approximating six at intake, but approaching only one symptom by year-two. Although results indicated that male and female participants differed significantly for mean number of conduct disorder symptoms at treatment entry, both groups reported mean symptoms exceeding the 3 required for diagnosis. By the year-two follow-up, no significant sex differences were demonstrated. The study also examined service utilization in the year following initial treatment exposure. Analyses sought to examine potential relationships between treatment duration or treatment focus (e.g., substance abuse treatment versus mental health services) and outcomes. In general, the results of the correlations and regressions showed that the nature or amount of treatment received failed to predict or account for differences in frequency of substance use, symptoms of mental distress, and conduct disordered or criminal behaviors